THE USE OF BIG CUBE GAME AS THE STRATEGY TO IMPROVE STUDENTS? VOCABULARY MASTERY - Zaitun .; Ananda Esa Fitri (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
The purpose of this research is to convey Big Cube Game  is effective in teaching vocabulary mastery. This research conducted in SMPN 3 Tangerang Selatan. The population of this research is seventh grade students, and the sample is 8.5 consists of 40 students. The method of this research is quantitative method and using pre ? experimental design. To collect the data, the researcher used pre ? test and post ? test that given to the students. The result score of the data indicated that, the total score of students in pre ? test were 2425 with the mean score was 60,62. The lowest score of pre ? test were 45 and the highest score were 90. The total score of students in post ? test were 3150 with the average were 78,75. The lowest score of post ? test were 65 and the highest score were 100. There is significance different from the result of pre ? test and post ? test score. The results of the pre-test and post-test were calculated using the manual statistically. And by using the t-test the results of t0 (4,47) are higher than the t-table at the significance level (p) = 0.05 (1,684). Thus it can be concluded that the Big Cube game has a significant strategy on the vocabulary mastery of students in class 8.5 at SMPN 3 Tangerang Selatan.